Interaction between mitochondrial oxidative stress and myocardial fibrosis in the context of diabetes - Pu-Hua Zhang; Nuo-Nan Li; Nuo-Nan Li; Xiang Gu; Chun-Xia Zhou; Zhen-Zhen Jiang; Xian-Jun Luo; Xian-Jun Luo; Hong-Wen Zhu; Xiao-Yong Zhu (Frontiers in Endocrinology)
Diabetes represents a global chronic health issue and has emerged as a crucial risk factor for cardiovascular diseases (CVD). Myocardial fibrosis (MF), which often accompanies diabetes, plays a pivotal role in the progression of cardiac dysfunction and heart failure (HF). Recent research has highlighted mitochondrial oxidative stress (OS) as a fundamental mechanism driving MF in diabetic conditions. Elevated blood glucose levels and metabolic imbalances lead to mitochondrial impairments, which in turn cause an excessive buildup of reactive oxygen species (ROS), culminating in OS. This OS not only inflicts direct damage on myocardial cells but also facilitates the proliferation of myocardial fibroblasts and collagen accumulation through the activation of specific signaling pathways, thus intensifying MF. Furthermore, MF itself intensifies mitochondrial OS, creating a vicious cycle that ultimately impairs myocardial structure and function. Thus, a thorough understanding of the interaction between mitochondrial OS and MF in diabetes is crucial for identifying effective therapeutic targets and enhancing the early diagnosis and intervention strategies for diabetic cardiomyopathy.